1981
DOI: 10.1128/iai.32.1.194-197.1981
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of bacteria to vaginal epithelial cells at various times in the menstrual cycle

Abstract: Adherence of vaginal isolates of Escherichia coli, Lactobacillus species, group B streptococci, Gardnerella vaginalis and Neisseria gonorrhoeae to exfoliated vaginal epithelial cells was studied in 10 healthy, sexually active medical students. Studies were done pre- and postmenstrually and at midcycle for two consecutive menstrual cycles. The mean number of adherent bacteria per vaginal epithelial cell (range) was 3.4 (0 to 14) for E. coli, 60.5 (12 to 152) for Lactobacillus species, 54.8 (21 to 76) for group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Second, while the bacterial cell density of G. vaginalis in vaginal fluid can reach 10 2 to 10 4 CFU/ml in a healthy vaginal community, this often increases to 10 5 to 10 8 CFU/ml during BV (35)(36)(37). Third, it expresses a number of virulence factors that are thought to contribute to its pathogenicity, including adherence to vaginal epithelial cells, the capacity to form a biofilm, and the production of the pore-forming toxin vaginolysin (VLY) (35,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). VLY has been the most extensively studied virulence factor of G. vaginalis due to its conserved nature within the species and its association with BV (48).…”
mentioning
confidence: 99%
“…Second, while the bacterial cell density of G. vaginalis in vaginal fluid can reach 10 2 to 10 4 CFU/ml in a healthy vaginal community, this often increases to 10 5 to 10 8 CFU/ml during BV (35)(36)(37). Third, it expresses a number of virulence factors that are thought to contribute to its pathogenicity, including adherence to vaginal epithelial cells, the capacity to form a biofilm, and the production of the pore-forming toxin vaginolysin (VLY) (35,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). VLY has been the most extensively studied virulence factor of G. vaginalis due to its conserved nature within the species and its association with BV (48).…”
mentioning
confidence: 99%
“…Sobel et al and Peeters et al both showed that adherence of Gardnerella vaginalis depends on pH of the vagina. [20][21][22] Zariffard et al studied whether Gardnerella vaginalis, lactobacilli, and Mycoplasma hominis could be detected in vaginal specimens, and also their relation to each other using quantitative real-time PCR. They concluded that there is an inverse relationship between Gardnerella vaginalis and lactobacilli suggesting that these findings could be developed into a new method in detecting a disturbed vaginal microflora.…”
mentioning
confidence: 99%
“…Mdrdh & Westrom (13) reported a difference in adherence of group B streptococci and Neisseria gonorrhoeae on the one hand and lactobacilli and other indigenous flora isolates on the other. Sobel et al (21) in their in vitro system reported a similar adherence capacity of these bacteria.…”
Section: Discussionmentioning
confidence: 73%
“…The factors which lead to the change in flora have still not been properly identified. Changing adherence of lactobacilli and other vaginal microbes to the epithelial lining of the vagina may be one factor regulating the vaginal ecosystem (13,21,26). Eschenbach and co-workers ( 5 ) have postulated that H,02 production of lactobacilli plays an important role in the homeostasis of the vaginal flora.…”
mentioning
confidence: 99%